Keadilan Substantif dalam Sengketa Agraria: Analisis Putusan Sleman dari Perspektif Maqāṣid al-Sharī‘ah - Toruan, Daniel Natanael Lumban; Djaja, Benny (Tasyri' : Journal of Islamic Law, 2025)
This article examines the issue of buying and selling land under the hand that creates tension between formal legality and substantive justice in agrarian justice practice, with a focus on Decision Number 291/Pdt.G/2021/PN.Smn in Berbah District, Sleman. The practice of buying and selling land without involving the Land Deed Making Officer (PPAT) and without registration at the Land Office is contrary to Article 37 paragraph (1) of Government Regulation Number 24 of 1997, so that legally positive cannot be used as a basis for the transfer of rights. This research uses a juridical-normative approach with a critical analysis of agrarian law norms, civil law rules, and maqāṣid al-sharī'ah—especially ḥifẓ al-māl (protection of property) and substantive justice (al-'adālah al-jawwāniyyah). The results of the study show that the panel of judges in the decision applied legal logic that is not only textual-formal, but also responsive to social realities and the good faith of the parties. This reflects an integrative effort in bridging normative law and the values of justice in society through the maqāṣid approach. This article emphasizes the urgency of reforming the understanding of public law and the need to reposition the role of the state in ensuring substantive justice in agrarian disputes involving small people.